1978
DOI: 10.1007/bf01408251
|View full text |Cite
|
Sign up to set email alerts
|

Isotope shift and configuration mixing in dysprosium II

Abstract: The isotope shift in the spark spectrum of dysprosium was studied by means of a photoelectric recording Fabry-Perot spectrometer with digital data output. For 29 lines the isotope shift of 162Dy and t64Dy was measured in order to check the mixing of the three configurations 4f95d6s, 4f95d 2, and 4fl~ calculated by Wyart. By means of the sharing rule the configuration mixing could be confirmed as a whole. In the ground state configuration the influence of relativistic effects was demonstrated and explained by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Two of the isotopes have odd Z and so have hyperfine splitting, but we couldn't find information on our transitions. We did find information on IS for most of our transitions in Aufmuth (1978). We used the solar system isotope ratios.…”
Section: Appendix Atomic Parameters Oscillator Strengths and Linelistsmentioning
confidence: 99%
“…Two of the isotopes have odd Z and so have hyperfine splitting, but we couldn't find information on our transitions. We did find information on IS for most of our transitions in Aufmuth (1978). We used the solar system isotope ratios.…”
Section: Appendix Atomic Parameters Oscillator Strengths and Linelistsmentioning
confidence: 99%
“…They also deduced the changes between isotopes in the mean square radius of the nuclear charge distribution given in Table 9.17. Attempts to disentangle the configuration mixing in Dy II by a study of isotope shifts have proved less satisfactory (Aufmuth, 1978). Aufmuth showed that crossed second-order effects and relativistic effects are present.…”
Section: Dysprosiummentioning
confidence: 99%
“…However, a J-dependence within one term could be demonstrated in several cases. Caused by 4f-electrons it was found in Sm I [3,4], Dy I [5], DylI [6] and ErI [7] but due to 5d-electrons only one example was reported so far: i.e. in EuI [8,9].…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, this investigation extends the determination of the J-dependence in the ionized spectra, for which only one investigation was published up to now, i.e. Dy II [6].…”
Section: Introductionmentioning
confidence: 96%